Defining occult injuries of the distal forearm and wrist in children. (June 2016) - Elvey, Michael; Patel, S.; Avisar, Erez; White, W. J.; Sorene, E.
Purpose: The nonspecific terms "wrist sprain" and "suspected occult bony injury" are frequently documented as diagnoses in occult paediatric wrist injuries. To date, however, no one has accurately defined their true underlying pathology. The primary objective of this study was to identify the true pathoanatomy of occult acute paediatric wrist injuries. Our secondary objective was to compare our findings with existing adult data in order to determine any population differences that might be clinically relevant. Methods: We performed a single-centre retrospective case series evaluating MRI findings in acute paediatric wrist injuries presenting to the hand injury unit between 2011 and 2014. All patients underwent standardised radiographs of the wrist and, where clinically indicated, of the scaphoid. Where no bony anomaly was identified, MRI scanning was offered. Cohen's kappa coefficient was used to calculate the agreement between clinical and MRI diagnosis. Results: 57 patients met the final inclusion criteria. Occult fractures and bony contusions comprised the majority of the pathologies, at 36.5 and 35.0 %, respectively. There were no cases of isolated soft-tissue injury. MRI effected management change in 35.1 % of cases. Paediatric wrists demonstrated differences in injury pattern and distribution when compared to an adult population. Conclusion: This study defines for the first time the true pathology of occult paediatric wrist injuries. The current definition of a wrist sprain was not applicable to a single case and therefore appears to be inappropriate for use in the paediatric population. A precise knowledge of the likely pathology facilitates accurate information delivery whilst reducing parental uncertainty and treatment variation.